Female‐biased sex ratio shifts in a solitary parasitoid and their effects on virginity, population dynamics, and biological control. Issue 1 (4th December 2012) - Wogin, Michael J.; Gillespie, David R.; Haye, Tim; Roitberg, Bernard D.
Abstract Mated female parasitic wasps can control the sex of their offspring by controlling which eggs are exposed to sperm. Females that have failed to mate, however, are restricted to producing only male offspring, as all their eggs are unfertilized. We incorporated the effects of these sometimes constrained, sometimes flexible parasitoid sex ratios into a basic Nicholson–Bailey population model. We found that the less common case of an increasing female bias in response to competition can destabilize dynamics and have both positive and negative effects on host suppression. We also incorporated the effects of virginity due to a lack of males into the model. Virginity had stabilizing effects on parasitoid‐host population dynamics, and prevented runaway female bias in a parasitoid population. We found that the changes in host suppression caused by these new behaviours can be either positive or negative, and are highly dependent on the search efficiency of the parasitoid.